PENGARUH PENERAPAN QUANTUM TEACHING TERHADAP MOTIVASI DAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SEKOLAH MENENGAH ATAS SYIHABUDDIN - Anita Anita (Conciencia, 2016)
The research was an experimental research with the method of Quasi Experimental Design. The problem in the research was; looking for the difference between learning motivation and learning outcomes of students who used Quantum Teaching method with conventional method and a positive relationship between the two by using Quantum Teaching method in PAI subject in class XI SMA Syihabuddin, Lubuk Tanjung. T-test two samples unpaired that there was difference in the average of motivation of experiment and control classes because the significance test was statistically where obtained scores ​​P = 0.000 <0.005 and the score of learning motivation of experiment class was the count t 6.085 and for the scores of learning motivation of control class were - 4.846. Therefore (Ha) was received and (Ho) was rejected. There were differences between student learning outcomes in PAI subject that was taught using the method of Quantum Teaching with that not using the method of Quantum Teaching because the significance test statistically which was obtained scores ​​P = 0.000 <0.005 and the scores of learning outcomes of experiment class were the count t 6.089 and for the cores of learning outcomes of control class were 4,040 score of the count t was 4> table t = 2. Therefore (Ha) was received and (Ho) was rejected. There was a positive relationship between learning motivation and learning outcomes of students in the PAI subject that was taught using the method of Quantum Teaching, then the count r =, 887. Then compared with rt that existed N = 38 by seeing the significance level of 1%= 0.429 with a significance level of 5% = 0.333 meant that ro was larger than rt, then the consequence was (Ha) received and (Ho) rejected. So the conclusion was that there was a significant positive correlation between the application of Quantum Teaching method between learning (XI) and learning motivation (X1) with the learning outcomes (X2).